The association of subtypes of breast cancer with tumour characteristics and reproductive factors in 1326 Mexican women - Pérez-Rodríguez, Gabriel; Aranda-Moreno, Catalina; Olivares-Corichi, Ivonne M.; Garcia-Sanchez, Jose R. (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study: In breast cancer, oestrogen receptor (ER), progesterone receptor (PgR), and HER2 (HER2/Neu) expression status are used to classify neoplasms into subtypes: Luminal A, Luminal B, HER2/Neu type, and Basallike. The aim of the present study was to establish the molecular subtypes of breast cancers and their association with tumour characteristics and reproductive factors in Mexican women. Material and methods : A total of 1326 biopsies of breast tumour tissues were analysed for ER, PR, and HER2/Neu by immunohistochemistry (IHC). Information regarding age, tumour characteristics, and node involvement profiles were collected. Results: IHC established that the most common subtype of breast cancer was Luminal A (64.93%), followed by Basal-Like (13.88%), Luminal B (12.52%), and HER2/Neu (8.67%). T2-size tumours (> 2 cm but < 5 cm) were present in 47.59% of all patients. Univariate analysis showed that lymph node positivity (p = 0.009), stage (p = 0.013), and placement of the tumour (p = = 0.001) were factors associated with breast cancer subtype. Conclusions : Our data show that IHC is useful for distinguishing different subtypes of breast cancer and that Luminal A is the most common breast cancer subtype in the Mexican population. All subtypes were associated with unfavourable clinicopathological features, suggesting that late diagnosis is an important contributor to high mortality rates in the Mexican population.